2020
DOI: 10.3389/fnagi.2020.585218
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cerebrovascular Loss in the Normal Aging C57BL/6 Mouse Brain Using in vivo Contrast-Enhanced Magnetic Resonance Angiography

Abstract: Microvascular rarefaction, or the decrease in vascular density, has been described in the cerebrovasculature of aging humans, rats, and, more recently, mice in the presence and absence of age-dependent diseases. Given the wide use of mice in modeling age-dependent human diseases of the cerebrovasculature, visualization, and quantification of the global murine cerebrovasculature is necessary for establishing the baseline changes that occur with aging. To provide in vivo whole-brain imaging of the cerebrovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 105 publications
(169 reference statements)
1
5
0
Order By: Relevance
“…6 ). In line with our finding are studies showing no change in striatal BV density between young and aged mice 62 , 63 . However, numerous reports confirm decreased cortical BV density with aging 64 66 ; indicating that BV density loss in the aging brain is likely region specific.…”
Section: Discussionsupporting
confidence: 93%
“…6 ). In line with our finding are studies showing no change in striatal BV density between young and aged mice 62 , 63 . However, numerous reports confirm decreased cortical BV density with aging 64 66 ; indicating that BV density loss in the aging brain is likely region specific.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have reported visualization of cerebral vasculature through MRA methods on ultra-high (≥7 T) magnetic fields. 1,[70][71][72][73] Pastor et al reported an optimized protocol for visualization of cerebral microvessels of rats using a repetition time of 60 ms and achieved an isotropic resolution up to 62 µm in 98 min of total imaging time at 11.7 T using 3D TOF angiograms. This protocol seems promising for cerebral MRA at ultra-high field MRI, however the time required to visualize the microvessels was surprisingly high which may introduce a challenge the need to keep animals under anesthesia for a prolonged scan.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebral vasculature plays a critical role in maintaining normal brain function and cognition, providing an uninterrupted supply of oxygen and nutrients, and thus alterations to blood supply could contribute to brain pathologies. 1,2 Cerebral angiography can help diagnose and track effective therapies for neurovascular diseases, and may eliminate the need for surgery. 3,4 A critical barrier to understanding cerebrovascular pathophysiology is the ability to accurately visualize microvas-cular networks and/or blood perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…A coronal axial multi-slice DWI sequence covering the entire brain was performed with the following parameters: TR = 3000 ms, TE = 32.5 ms, matrix size = 96 × 96, slice thickness = 0.75 mm. Apparent diffusion coefficient (ADC) values were acquired by placing four circular regions-of-interest (ROIs) within various brain and spinal cord regions, with values averaged [ 80 ].…”
Section: Methodsmentioning
confidence: 99%